Street crossing by typically developed children in real and virtual environments. - Bart O; Katz N; Weiss PL; Josman N (OTJR: Occupation, Participation & Health)
Independent street crossing is a necessary skill for children to have so they can engage in different occupations and complete tasks such as arriving at school or after-school activities. Without the appropriate opportunities to practice and master street crossing, children's participation will be incomplete and they will not be able to attain their physical, emotional, and intellectual potentials. Training children in safe street crossing is especially important because pedestrian injury is the second leading cause of death and serious injury among children between 5 and 14 years old. The existing methods for teaching children how to cross a street safely are difficult to transfer to real-life situations. The purpose of the current study was to evaluate the effectiveness of a virtual reality environment in teaching children how to cross a street safely. Eighty-six typical children (55 girls and 31 boys) between 7 and 12 years old participated in the study. The children who failed the virtual reality test were randomly assigned to training and control groups. The children were observed while crossing a real street and tested within the virtual environment both before and after the virtual reality training. Results indicate that children in the training group significantly improved their street crossing abilities in both the virtual reality simulation and the real street crossing in comparison to the control group. Street crossing became safer with increasing age, but no differences were found between boys and girls. This low-cost and readily available street crossing simulation had a positive effect on children's street crossing behavior in the real environment and on their self-reported satisfaction. These results provide support for the potential of training in a virtual street crossing simulation to transfer to actual street crossing.